Photoprotective Effect of Ultrasonic-Assisted Ethanol Extract from Sargassum horneri on UVB-Exposed HaCaT Keratinocytes - Kirinde Gedara Isuru Sandanuwan Kirindage; Arachchige Maheshika Kumari Jayasinghe; Chang-Ik Ko; Yong-Seok Ahn; Soo-Jin Heo; Eun-A Kim; Nam-Ki Cho; Ginnae Ahn (MDPI AG, 2024)
The present study investigated the photoprotective effect of the ultrasonic-assisted ethanol extract (USHE) from Sargassum horneri, a brown seaweed containing fucosterol (6.22 ± 0.06 mg/g), sulfoquinovosyl glycerolipids (C23H43O11S, C25H45O11S, C25H47O11S, C27H49O11S), and polyphenols, against oxidative damage in ultraviolet B (UVB)-exposed HaCaT keratinocytes. USHE indicated antioxidant activity in ferric-reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. After screening experiments, 15.6, 31.3, and 62.5 µg/mL concentrations of USHE and ascorbic acid as positive control were selected to be used throughout the investigation. USHE increased cell viability by markedly reducing the production of intracellular reactive oxygen species (ROS) in UVB-exposed HaCaT keratinocytes. Additionally, USHE reduced the apoptosis and sub-G1 cell population and increased the mitochondrial membrane potential. Moreover, USHE modulated the protein expression levels of anti-apoptotic molecules (Bcl-xL, Bcl-2, and PARP) and pro-apoptotic molecules (Bax, cleaved caspase-3, p53, cleaved PARP, and cytochrome C). This modulation accorded with the upregulation of cytosolic heme oxygenase (HO)-1, NAD(P)H quinone oxidoreductase 1 (NQO 1), and nuclear factor erythroid-2-related factor 2 (Nrf2), collectively known as components of the antioxidant system. These findings suggest that USHE has a photoprotective effect on UVB-exposed HaCaT keratinocytes and can be utilized to develop cosmeceuticals for UVB protection.